Beta-alanine supplementation seems to increase physical performance and acute recovery in competitive judokas - Raul Lopez-Grueso; Adolfo Aracil Marco; Jose Manuel Sarabia Marín; Carlos Montero Carretero (Asociación Española de Ciencias del Deporte, 2014)
Introduction: This paper aims to test whether supplementation with beta-alanine (BA) increases performance in judo. Method: A simple-masked, quasi-experimental study was performed. Five judokas of the Spanish National Team were distributed into two groups: a) placebo (PLA, n= 3) and b) experimental (BA, n= 2). Participants performed the SJFT before (PRE) or after (POST) a period of 35 days of supplementation with 6 g day-1 of maltodextrins (PLA) or BA. During testing and recovery, the following variables were measured: a) heart rate; c ) number of projections; d) blood lactate; e) rating of perceived effort and f) rating of recovery. Results: At the evaluation POST, SJFT index improved by 10.1 ± 1.7% in the BA group, and by 3.9 ± 3.9% in the PLA group. This improvement was due to the increase in the number of projections, which was accompanied by higher values of blood lactate. Similarly, judokas at the BA group showed faster recovery. Discussion: Beta-alanine supplementation for 35 days appears to improve performance in judo, possibly due to the greater involvement of lactic acid metabolism.